(3GdefY ef GdJUQa ai GdELQGAGJ GdLfGFjI (B: s (3OQGSI ebGQfI (B/ s - (3QRb SYO Ydi YHOGdeLjOs; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JMJGL OQGSI GdefY ef GdJUQa ai GdELQGAGJ GdLfGFjI cOQGSI ELQGFjI eJNUUI h eJYebI ai GdbGfhf GdLfGFi Edi abg JbOjQi jJUOi ddeSCdI efGW GdHMK ef NdGd efgL JMdjdj Jbhjei jbhe Ydi GdGSJbQGA h GdGSJfHGW eYkG MJi jecf GdhUhd HGdOQGSI dZGjJgG(B: (3ef NdGd JMdjd eG gh bGFe ef GdfUhU GdLfGFjI GdeJYdbI HehVhY GdHMK h JbOjQ eG EPG cGfJ bO MbbJ gOa GdehGRfI Hjf MeGjI Mbhb GdCaQGO h MQjGJge ef fGMjI h eUdMI GdeLJeY ef fGMjI CNQi HeG jMbb GdYOGdI HMjK dG jbY GYJOGA ef Ci eUdMI Ydi CNQi(B. (3h ef gPG GdefWdb dGHO ef OQGSI GdehVhY ef NdGd GdfUhU GdbGFeI HGdaYd ai GdbGfhf GdeUQi h GdaQfSi h HYV GdGJaGbjGJ GdOhdjI(B: (3eY eYGdLJgG habkG deYGjjQ Mbhb GdEfSGf GdOGNdjI h GdOhdjI(B: (3ai SHjd JfGhd gPg GdOQGSI jJe GSJNOGe GdefgL GdJMdjdi GdebGQf dHMK GdfbGW GdSGHbI(B. (3h JJeKd CgOGa GdOQGSI ai GdfbGW GdCSGSjI GdBJjI(B: (3GSJLdGA eaghe TGed dELQGA GdefY ef GdJUQa cCMO GdELQGAGJ GdJi JJNP chSjdI dEfLGM GdOYhi GdLfGFjI ai JMbjb CgOGagG dGSjeG ai LQGFe GdCehGd GdYGeI(B: (3HGdJYQa Ydi eGgjI ELQGA GdefY ef GdJUQa h GdEOGQI h GdJfXje GdbGfhfi dgPG GdELQGA ai GdbGfhf GdeUQi h GdebGQf(B: (3h OQGSI eOi GdJhGab eY GdeHGOF GdOSJhQjI PGJ GdUdI HGdSjGSI GdLfGFjI(B. (3Gdhbha Ydi GdbhGYO GdbGfhfjI GdebQQI ai HYV GdehGKjb GdOhdjI h GdJi JJYdb HGJNGP ELQGA GdJLejO Ch GdMLR ddCehGd GdeJMUdI ef GdLQGFe(B: (3h eOi GdJhGab Hjf GdJTQjY GdeUQi h gPg GdbhGYO h eOi caGjI gPg GdELQGAGJ ddEMGWI HCehGd GdLQjeI hedGMbJgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B303-328s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdELQGAGJ GdLfGFjI s; (3GdJUQa s; (3GdefYs; (3eGgjI GdefY ef GdJUQas; (3GdefY ef GdJUQa aj Gdabg GdGSdGejs; (3GdfjGHI GdYGeIs; (3GdLgGJ GdGOGQjIs; (3GdbVGA GdeSJYLds; (3LQjeI GdcSH GdeTQhYs; (3ENaGA GdGehGd ZjQ GdeTQhYIs; (3JLejO hGSJQOGO GdGehGd GdegQHIs; (3VeGfGJ GeQ GdefY ef GdJUQas; (3MeGjI GdZjQ MSf GdfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs